Factors affecting effective management of the mineral development fund in three selected districts in Ghana - Azadi-dor, Emmanuel Deyo (University of Cape Coast, 2020)
The Government of Ghana in 1993 by an Executive Fiat established the Mineral Development Fund (MDF) to enable the District Assemblies which host mining operations to undertake development projects to mitigate the effects of mining in affected communities. The purpose of this ex-post, quasi experimental design using proxy pretest, survey and focus group discussions is to undertake an evaluation of the programme since its inception to assess the factors affecting effective management of the Mineral Development Fund in Tarkwa, Prestea Huni Valley (PHV) and Obuasi District Assemblies who have received GH₵17,673,830.25, GH₵18,277,241.00 and GH₵10,922,654.89 respectively. A total of 211 projects were examined and the factors identified to be affecting the effective management of the MDF include Districts adding the fund to IGF, several discrepancies in royalty disbursements and Districts receipts, no technical risk assessment to identify the harmful effects of mining, low efficiency rates, project cost and time variations, misappropriation, misapplication, mis-targeting of beneficiaries and carrying out frivolous projects. In Super DEA analysis Obuasi District is the most efficient. Direct logistic regressions were performed and the models correctly classified 69.9%, 85.5% and 88.7% of the cases for Tarkwa, PHV and Obuasi Districts respectively as effective projects. The ranking of the factors which affect the effectiveness of infrastructure projects by key stakeholders indicated adequate funding, adequate plans and specifications, political influence, Project Manager’s competence, constructability and risk management as the top six factors to be taken seriously throughout the project life cycle. It is therefore recommended that there should be timely collection and disbursement of the Fund; risk analysis be done to identify MDF related projects; Officials who have misapplied the Funds be sanctioned; an agency be set up to manage the Fund at the District level; key stakeholders, especially the affected communities, be involved in all stages of management of the MDF. Finally, a law should be passed to provide clear guidelines as to the collection, disbursement and management of the MDF in order to achieve its objective.
xv,278p:.ill
Keywords: District Assemblies; Effectiveness; Efficiency; Evaluation; Mineral development Fund; Projects